Avgangsutstillingen 1999 : Kunsthøgskolen i Oslo Statens Kunstakademi. - Cooke, Lynn; Schmidt, Staffan; Stenersenmuseet, Oslo (Oslo : [s.n.], 1999)
Bjertnaes, Sverre Koren ; Eriksen, Helen Karen ; Peña, Kristin Falck ; Granbo, Monica ; Hanssen, Anita H ; Johanssen, Ingegerd ; Lundström, Nina ; Moe, Marius ; Pennington, Liv ; Pihl, Thomas ; et al.
Stenersenmuseet, Oslo, 29.05.1999 - 20.06.1999
kunstcatalogus